Atomic data for iron-group elements of astrophysical interest - Nave,G; Sansonetti,CJ; Pickering,JC; Ruffoni,M; Thorne,AP; Liggins,F (2013)
The joint project between NIST and Imperial College London to measure spectra of singly-ionized iron-group elements using Fourier transform and high-resolution grating spectroscopy is described. © 2013 AIP Publishing LLC.